Comparative Analysis of Multi-Substrate Materials in Microstrip Antenna Models for Broadband Wireless Communications - Herdiana, Budi (International Journal of Electronics and Communications Systems, 2022)
Multi-substrate antenna material is a combination of more than one primary antenna base material where this substrate material can determine the quality of antenna performance. A quantitative empirical approach is carried out to achieve maximum performance by processing the dielectric constant of the substrate to obtain other antenna parameters. This aims to increase the stability of the antenna gain and produce a large bandwidth. The results show that diamond has a bandwidth of 75 MHz with a maximum gain of 4.228 dBi and a VSWR of 18.017. While epoxy FR-4 produces a bandwidth of 57 MHz with a maximum gain of 3.444 dBi and a VSWR of 2.011, the quartz material produces a bandwidth of 80 MHz with a maximum gain of 4.426 dBi and a VSWR of 10.884. The conclusion is that FR-4 epoxy substrate performs better than diamond and quartz. It is hoped that the results of this research will impact the development of a smart antenna system.